Special Issues Relating to Corporate Governance and Family Control - Morck, Randall; Yeung, Bernard (World Bank, Washington, D.C., 2013)
Control of corporate assets by wealthy families in economies lacking institutional integrity is common. It has negative implications on corporate governance and adverse macroeconomic effects when it extends across a sufficiently large part of the country's corporate sector. The authors consider the reasons why family control and control pyramids predominate in emerging market economies and in some industrial economies. They also discuss the reasons why widely held freestanding firms predominate in the United States. The authors discuss policies that countries might adopt to discourage family control pyramids, but caution that control pyramids are but one feature of an institutionally deficient economy. A concerted effort to improve a country's institutions is needed before diffuse ownership is desirable.